ВЛИЯНИЕ МАГНИТНОГО ПОЛЯ НА КОЭФФИЦИЕНТА НЕИДЕАЛЬНОСТИ ВАХ ДИОДА - Гулямов, Г.; Умаров, К.Б.; Мухитдинова, Ф.Р.; Солиев, А.З. (SCIENCE and SOCIETY, 2024)
The influence of the magnetic field was calculated on the nonideality coefficient of the current-voltage characteristic. It has been established that, as a result of injection into the magnetodiode, the formation of nonequilibrium charge carriers leads to an increase in the height of the potential barrier and a decrease in the concentration of charge carriers. This reduces the current passing through the diode, increases the base resistance and leads to a change in the non-ideality coefficient of the diode’s current-voltage characteristic.